The Influence of the Image-Assisted Student Team Achievement Division (STAD) Learning Model on the Ability to Write Description Text in Class VII Students of MTs Annur Palembang - Fitri Yanti; Yessi Fitriani; Indah Puspa Utami (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
The purpose of this study was to determine whether there is an influence of the image-assisted STAD learning model on the ability to write description text in grade VIII students of MTS Annur Palembang. Methods used using quantitative experimental methods, on data collection techniques using observation, documentation and test techniques. The test is in the form of writing description text. The samples taken in this study amounted to two classes, namely the control class and the experimental class. In the control class there were 29 people and in the experimental class there were 30 people. Based on this study, the results of the hypothesis test using the SPSS application obtained a sig value (2 tailed) of 0.000 < 0.05, it can be concluded that there is a significant difference in the average results of writing description texts for grade VII students carried out in the control class and experimental class using the image-assisted STAD model applied in the experimental class and without using the p model Based on the hypothesis test table and the average value of the control class and experimental class, it can be concluded that Ha was accepted and Ho was rejected, this shows that there is a significant influence on the effect of the image-assisted Student Team Achievment Division (STAD) Learning Model on the ability to write description text in grade VII students of MTs Annur Palembang.